تمرينات مركبة مقترحة بتتالي المثيرات وتاثيرها في بعض مظاهر الانتباه والمهارات الاساسية لدى لاعبي الكرة الطائرة - جمعة محمد عوض; عبد الله حميد صالح (الرياضة المعاصرة, 2018)
Compound Exercises proposed successively stimuli and their impact on some aspects of attention and basic skills of volleyball game for Youth. The study aimed to identify the concentration level, divert attention, basic skills of Volleyball sample, preparing compound exercises of successively stimuli and learn about the impact of this exercise in the development of the research sample .The researchers carried out his study on the sample by the players of Anbar and Habbaniyah Youth club and the rate of (24) players. The previous measurements for variables are carried out which were chosen from the group work according the right scientific styles. Then applied the preparing training which prepared by the researchers for (12) weeks, in (2) training units in a week, Then, at the same way carried out the after measurements. Then, a count the information and the results and treated them statistically and presented them in schedule and discussed them scientifically according to the scientifically sources, The researchers conclude that compound exercises successively stimuli were active in the development of the variables entry study, The development rates of the experimental group were better than the control group, and it's recommended to focus on compound exercises successively stimuli and part of the training programs Volleyball should be for young.